An Economical and Ultra Dense WDM-PON System with Polarization Interleaving and PWR. Issue 1 (1st August 2022) - Sachdeva, Shippu; Bansal, Mohit
Abstract: In this paper, a cost effective and easy maintenance based dispersion compensation technique is proposed in ONU of the wavelength reused wavelength division multiplexing reliant passive optical network. Moreover, in order to suppress intra-channel crosstalk DQPSK is employed for downstream and for inter-channel crosstalk suppression, polarization interleaving is used in the system. Furthermore, for the investigation of proposed system in terms of dispersion reduction, three different scenarios are considered such that system with only DCF, linearly chirped FBG and joint module of DCF+FBG. System has total 4 channels and each has bit rate of 20 Gb/s with 25 GHz channel spacings. It is observed that joint module of DCF+FBG has maximum ability to compensate dispersion and linearly chirped FBG has least performance. Proposed joint technique for pulse width reduction in ONU is cost effective, highly efficient to combat with pulse width reduction issues and also needs very less maintenance.